Epstein-Barr Virus and DNA Methylation in Gastric Cancer - Ayşe Feyda Nursal (İstanbul Medical Journal, 2016)

(untitled)
Gastric cancer (GC) is the fourth most common type of malignity and the second leading cause of cancer death worldwide. Infectious agents such as Helicobacter pylori (H.pylori) and Epstein-Barr virus (EBV) play important role in the etiology in GC. EBV is a double-stranded DNA virus, approximality 184 kb in size, included in Herpes virus family and is the first virus determined in human neoplastic cell. EBV associated gastric cancer (EBVaGC) constitutes approximately 10% of whole GC in wordlwide. DNA hypermethylation in promotor region of tumor supressor genes is seen frequently in the genetic basis of EBCaGC. It is not a clear subject how EBV infection induce the methylation. In this review, the current literature about the gene promotor region hypermethylation in EBVaGCs will be revised.